Clement Comer Clay, Digest of the Laws of Alabama 413, § 8 (1843) - (:unkn) unknown (My University, 1843)
Prohibited fighting or discharging a firearm or air-gun in any city, town, or militia muster, or public assembly. Violators fined not less than one hundred nor more than five hundred dollars, or imprisoned not exceeding six months, or both at the discretion of the judge.
Keywords: DISCHARGE; DUELING